The Effectiveness of Using Self – Assessment on Student Writing Achievement - Arni Fitri; Abdul Aziz Rifaat (Institut Agama Islam Negeri Palopo, 2022)
This research used pre-Experimental Design using quantitative approach with one group pre-test and post-test design. It is intended to find out any the significant differences scores of the students before and after taught using Self-Assessment. The population of this study was all the First Semester of S1 Pharmacy Study Program. Whiles, the sample was consisted of 43 students. Based on posttest score of calculating SPSS the mean score 82.81, which means that the average of 43 students are get score is 82.81, indicated that the students can mastery writing well. Based on statistical calculation using SPSS 25.00 for windows, the researchers knew that the difference mean score of pre-test and post-test is 14,3489. The sig (2-tailed) or the p value (two-tailed) is 0.000. Given that the present test is one-tailed test, so the Sig. (2- tailed) or the p value (0.000) is divided by two: 0.000/ 2 = 0.000, and the significance level (α) was 0.05. Since 0.000 is smaller than significance level (α) 5%. The conclusion is that self-assessment is effective toward student’s writing achievement.